THE EFFECT OF SPECIAL EXERCISES AND BETA-CAROTENE INTAKE ON SOME PHYSICAL VARIABLES AND RECOVERY SPEED FOR 400-METER HURDLES ATHLETES - Hussein, Ali Abdulameer (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
Nutrition plays a major role in the recovery process and replenishes energy sources for players. It also works as antioxidants and improves the level of players. Therefore, the research study aimed to prepare exercises accompanying beta-carotene intake to improve the recovery process and some physical variables for 400-meter hurdles players. The research community included 400-meter players at Ain Al-Tamr Club. The athlete - Iraq - Al-Ghadhariya, which numbered 10 players. The research sample was divided into two experimental groups (control) and experimental, equally. The researcher used special exercises (recovery) at the end of the main part of the training unit for the coach, with a time of approximately (15) minutes. The recuperative exercises were used, including the Massage using (roller, cold compresses, ice bags) and aerobic exercises (stretching the muscles) for the purpose of accelerating the recovery process after the great effort of the training units, while taking beta-carotene in one dose daily. The first experimental group (control) used recovery exercises only, relying on the instructions of the trainer from The nutritional program also used the same exercises for the second experimental group, along with taking a dose of beta-carotene after lunch every day for one month and under the supervision of a specialist doctor. The researcher concluded. The recovery exercises prepared by the researcher, accompanied by beta-carotene as an antioxidant, have a clear positive impact on the recovery process and the improvement of variables through the development that occurs in the level of strength endurance and speed endurance of the players. Eating carotene contributed to improving the maximum level of oxygen consumption, so the researcher recommends that players take nutritional supplements and antioxidants to compensate for the deficiency in meals, especially beta-carotene as an antioxidant because of its major role in the player’s recovery processes.